Affirmative action or just discrimination? A study on the endogenous emergence of quotas - Loukas Balafoutas; Brent J. Davis; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
Affirmative action rules are often implemented to promote women on labor markets. Little is known, however, about how and whether such rules emerge endogenously in groups of potentially affected subjects. We experimentally investigate whether subjects vote for affirmative action rules, against, or abstain. If approved by the vote, a quota rule is implemented that favors women in one treatment, but members of an artificially created group based on random color assignment in another treatment. We find that quota rules based on gender are implemented frequently and do not affect the performance of men and women in a contest. Quota rules based on an arbitrary criterion, however, are less often approved and lead to strong individual reactions of advantaged and disadvantaged group members and to efficiency losses. These results show that the effects of affirmative action policies largely depend on whether these policies are viewed favorably within the affected groups.
Keywords: C91; C92; D03; 330; affirmative action; competition; discrimination; experiment; voting